Challenges to policy implementation in renewable energy development in Nigeria - Yamusa, Shehu Usman; Ansari, Abdul Haseeb; Mustafa, Maizatun (penseejournal.com, 2013)
Nigeria, rich in oil and gas, is among the top ten oil producing countries worldwide and plays a vital role in the Organization of the Petroleum Exporting Countries (OPEC). It has over 33 billion bbl oil reserves with 2.7 billion tonnes of coal reserves as conventional energy sources. It also has tremendous potential for renewable energy sources such as small hydropower, solar energy, wind energy and biomass energy. Yet the country does not have enough power supply to sustain its economic development. Sustainable economic development is engendered though sustainable energy and sustainable power generation from all sources. Where there is no sustainable power generation, the country’s economic growth and per capita GDP will go on declining. In view of this, this paper examines the issues pertaining to capability of power generation and energy demand and makes special reference to efforts that have been made so far in that area in the country. The paper further examines a number of challenges the country is facing in the implementation of its energy policy and laws by various government agencies.